Perlindungan Konsumen terhadap Tindakan Pemadaman Listrik yang Dilakukan Secara Sepihak oleh PT. PLN (Persero) UP3 Bali Selatan - I Gede Dharma Kusuma; I Nyoman Putu Budiartha; lda Ayu Putu Widiati (Warmadewa Press, 2021)
Circumstances that make people complain about the services provided by PLN are power outages without prior notification. The number of public complaints related to power outages has forced PLN to be confused in fixing the organizational structure, especially in the coordination sector between workers. The purpose of this research is to reveal the legal protection arrangements for consumers of electricity users at PT. PLN (Persero) UP3 as well as legal remedies that can be taken by consumers using electricity in the event of a power outage unilaterally by PT. PLN Persero UP3 South Bali. This research method uses an empirical method with a statutory approach and a case approach. Data collection techniques were carried out by means of field research by applying the interview method. Sources of data used in the form of primary and secondary data sources. The data analysis technique was carried out systematically. The results of the research reveal that the government in terms of providing protection to the public to obtain electricity supply is sufficient to make consumer protection regulations in which there are consumer rights and obligations to obtain justice and are obliged to make appeals from the government in an effort to prevent criminal acts in accordance with positive law in force in Indonesia. The government is dealing with field workers from PLN who intentionally or unintentionally do not notify the public of this rotating power outage and PLN should give a warning to its workers who do not carry out orders according to the SOPs applicable in the company.